Dijkstra algorithm for nearest route determination and estimated cost of official travel - Alam, C N; Muzaki, F; Irfan, M; Dauni, P; Ramdhani, M A; Rahman, A (Journal of physics. Conference series, 2019)
The purpose of this Decision Support System (DSS) design is to analyze the nearest route of a position, which then carried out financing analysis for transportation to the specified location. The design methodology of this study is the Android-based application system by utilizing the mapping of the region on the hardware in the form of a smartphone. The analysis model chosen for this DSS is Dijkstra algorithm. The subject of system user is Coordinator of Islamic Higher Education (KOPERTAIS) region II for West Java and Banten. The design results show the good system capabilities of the system to select and determine the nearest route and estimate the cost of official travel so that official travel can be efficiently done based on the time and cost perspective.